Pengaruh Faktor Permodalan Dan Risiko Likuiditas Terhadap Profitabilitas Yang Dimediasi Risiko Pembiayaan Pada Bank Syariah - Soni Cahya Riyadi; Fatwa Choiron; Edwin Rega Prayogo (AKUA: Jurnal Akuntansi dan Keuangan, 2022)
Profitability is a performance indicator that describes a bank's ability to manage its assets into profit. The purpose of this study was to examine the effect of the analysis of the influence of capital factors and liquidity risk on the profitability of Islamic commercial banks in Indonesia mediated by financing risk. This study uses data on the annual financial statements of Islamic Commercial Banks Registered and Supervised by the Financial Services Authority for the 2014-2019 period. By using the Purposive Sampling method with a sample of 10 banks. The analytical method used is multiple linear regression analysis. The results showed that the capital factor had a negative and significant effect on financing risk, liquidity risk had no significant effect on financing risk, capital and liquidity risk factors together had a significant effect on financing risk and risk had a significant effect on profitability.